2004
DOI: 10.1038/emm.2004.36
|View full text |Cite
|
Sign up to set email alerts
|

Molecular technology and the recombinant TSH have changed diagnostics of thyroid carcinoma with positive I-131 whole body scan but low serum thyroglobulin

Abstract: Abbreviations: DTC, differentiated thyroid carcinoma; Tg, thyroglobulin; TSH, thyroid stimulating hormone; WBS, whole body scan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…The positive cut-off of TgAb (100 IU/mL in the current study) chosen for evaluation of DTC patients is controversial. Previous studies have reported that the cut-off level for TgAb ranges from 30 to 100 IU/mL [7,11]. Chung et al reported that using a cut-off level of 100 IU/mL, the recurrence rate in TgAb-positive patients (Tg-undetectable) was significantly higher than that in TgAb-negative patients (49 vs. 3.4 %, P \ 0.0001) [20].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The positive cut-off of TgAb (100 IU/mL in the current study) chosen for evaluation of DTC patients is controversial. Previous studies have reported that the cut-off level for TgAb ranges from 30 to 100 IU/mL [7,11]. Chung et al reported that using a cut-off level of 100 IU/mL, the recurrence rate in TgAb-positive patients (Tg-undetectable) was significantly higher than that in TgAb-negative patients (49 vs. 3.4 %, P \ 0.0001) [20].…”
Section: Discussionmentioning
confidence: 95%
“…However, discordant results (elevated level of sTg with negative 131 I-WBS or low levels of sTg with positive 131 I-WBS) can also occur [11]. A low level of sTg with positive 131 I scintigraphy is a relatively rare entity in clinical practice and it has been reported that 8.5 % of DTC patients show recurrences and metastases on RxWBS with a low sTg value [7].…”
Section: Discussionmentioning
confidence: 96%
“…This so-called false-negative Tg determination phenomenon can be explained by the following several reasons. [ 16 , 17 ] First, technical issues might cause a false Tg-negative result. In particular, antigen levels 10 to 10,000 times the upper limit of the assay range can exceed the binding capacity of antibody for the solid support.…”
Section: Discussionmentioning
confidence: 99%
“…Κλινική εξέταση της τραχηλικής περιοχής. [121]. Τα τελευταία χρόνια γίνεται λόγος για αποφυγή διενέργειας ολοσωματικού σπινθηρογραφήματος ως ρουτίνα και εφαρμογή του μόνο σε περιπτώσεις όπου ανευρίσκονται αντιθυρεοσφαιρινικά αντισώματα ή σε περιπτώσεις που δεν μπορεί να διενεργηθεί προσδιορισμός της θυρεοσφαιρίνης με χρήση rhTSH [189,111,202,9,140,190].…”
Section: πρώτο στάδιο μετεγχειρητικής παρακολούθησηςunclassified
“…Η μέτρηση αυτή πρέπει να γίνεται με σύγχρονες ανοσοχημικές μεθόδους προσδιορισμού, με λειτουργική ευαισθησία <1 ng/ml. Πολύ χαμηλά (<5 ng/ml) ή μή ανιχνεύσιμα επίπεδα θυρεοσφαιρίνης σε αυτή τη φάση συνηγορούν προς πλήρη ίαση από τη νόσο, τουλάχιστον σε ποσοστό 95,9%[121,138].…”
unclassified